Building Trust in Human-Machine Partnerships. Issue 39 (November 2020) - Canal, Gerard; Borgo, Rita; Coles, Andrew; Drake, Archie; Huynh, Dong; Keller, Perry; Krivić, Senka; Luff, Paul; Mahesar, Quratul-ain; Moreau, Luc; Parsons, Simon; Patel, Menisha; et al.
Abstract: Artificial intelligence (ai ) is bringing radical change to our lives. Fostering trust in this technology requires the technology to be transparent, and one route to transparency is to make the decisions that are reached by ai s explainable to the humans that interact with them. This paper lays out an exploratory approach to developing explainability and trust, describing the specific technologies that we are adopting, the social and organizational context in which we are working, and some of the challenges that we are addressing.